Efektivitas Pengendalian Piutang Untuk Mengantisipasi Terjadinya Piutang Tak Tertagih Pada Hotel Melia Bali Pada Tahun 2020-2022 - Komang Intan Cahyani Devi; Ni Made Suci; I Nengah Suarmanayasa (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
aims to analyze the effectiveness of receivables management in minimizing the risk of uncollectible accounts that impact the financial stability of the hotel. The study employs the COSO framework, encompassing five key elements: control environment, risk assessment, control activities, information and communication, and monitoring. The results indicate significant challenges in receivables management at Hotel Melia Bali, as reflected in the increasing value of uncollectible accounts over the years. In 2020, the proportion of uncollectible accounts to revenue reached 6.71%, rising to 7.94% in 2021, and surging to 11.37% in 2022. Analysis reveals that although revenue increased, receivables management was suboptimal, highlighting the need for improved control systems. The implications of this research include the necessity for stricter credit policies, optimization of collection procedures, and continuous monitoring of receivables. With more effective receivables management, Hotel Melia Bali is expected to enhance operational efficiency and maintain financial stability